SOCIAL SPORTS: IN SEARCH OF THE CONCEPT AND GUIDELINES FROM THE PERSPECTIVE OF THE PROFESSIONAL PHYSICAL EDUCATION PROJECT PARTNER ATUANTE SPORT IN THE CITY OF RIO DE JANEIRO. (Fiep Bulletin - online, 2011)
According to the available literature there is some doubt in the conceptualization of the term "Social Sports. Part of this doubt can be attributed to the absence of explanatory text that defines and promotes best among professionals of physical education a reflection on the subject. It is also noticed the lack of a standard that will be used by everyone in this area and is able to guide the studies in Physical Education and Sports. Thus, this work has endeavored to conceptualize the term social sport from what the professional feel, there, and especially experiences in their daily work. To this end, we asked 70 physical education professionals who campaign with sport in social projects describe on the topic. Used as an instrument questionnaire adapted from Go Tani (2007).Based on the arrays pointed out that the objective social sport, social inclusion, aimed at the participation, it deals with values, is concerned about socialization, undergoes playfulness, is focused on equity, and emphasizes leisure results in integration. Therefore, the data collected suggest a reference for researchers and professionals working in this area.
Keywords: Sports; Physical Education; Social Sport